IDENTIFICATION OF THERMOTOLERANT LINES IN RICE (ORYZA SATIVA L.) USING STRESS INDICES - Ramana Rao P V; Satish Y (The Journal of Research ANGRAU, 2025)
Stress from high temperatures is a significant environmental factor influencing crop yield. A diverse set of rice germplasm consisting of 48 genotypes (released rice varieties, advanced breeding lines along with tolerant (Nagina 22) and susceptible (Vandana) checks) was grown at two different conditions (Control and Heat stress conditions) in Kharif 2023 Under heat stress conditions, the genotypes showed a significant reduction in grain yield. Yield-based indices were computed using grain yield data collected under control and heat stress conditions. The Stress Tolerance Index (STI), Geometric Mean Production (GMP), Mean Production (MP), Yield Index (YI), Heat Index (HI), and Modified Stress Tolerance (K1STI and K2STI) were all positively and significantly correlated with yield under control and high temperature stress conditions, making them suitable indices for screening rice genotypes under high temperature conditions. Highest correlation was observed in STI, GMP, and MP with Ys (Yield under heat stress)under both control and heat stress conditions.The genotypes IET 28960, MTU 1153, MTU 1156, N 22, NLR 3778, L 663 and MTU 1290 highest mean rank and a lower standard deviation of rank, hence they can be identified as heat tolerant genotypes.